Atraumatic Care Pada Anak Yang Menjalani Hospitalisasi: Literature review - Meri Anggryni (MOLUCCAS HEALTH JOURNAL, 2022)
This study aims to description of atraumatic care in children with hospitalization. The method used in this researc is literature study using the online databased Google Scholar, EBSCO, Pubmed and Proquest. The search keywords are atraumatic care; hospitalization; pediatrics; child. The results showed, the implementation of atraumatic care is play therapy proved to have an effect on reducing anxiety in children with hospitalization. Play therapy that can be applied to children in hospitals is coloring, medical play, constructive play, origami, storytelling, playing clay, audiovisual, lego, and snakes and ladders. Atraumatic care; play therapy is the most therapy for children whi have managed hospitalization.